1998
DOI: 10.1016/s0378-7788(98)00023-1
|View full text |Cite
|
Sign up to set email alerts
|

Office worker response to an automated Venetian blind and electric lighting system: a pilot study

Abstract: A prototype integrated, dynamic building envelope and lighting system designed to optimize daylight admission and solar heat gain rejection on a real-time basis in a commercial office building is evaluated. Office worker response to the system and occupant-based modifications to the control system are investigated to determine if the design and operation of the prototype system can be improved. Key findings from the study are: (1) the prototype integrated envelope and lighting system is ready for field testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(54 citation statements)
references
References 3 publications
0
52
0
2
Order By: Relevance
“…The results suggested that occupant satisfaction increased with the semi-automatic and manual modes of operation [66]. Eighty-five percent of the participants judged the overall lighting to be comfortable in the manual mode, while 78% felt similarly about the semi-automatic mode, and 57% about the automatic mode.…”
Section: Integrated Lighting and Shading Control Systemsmentioning
confidence: 94%
See 1 more Smart Citation
“…The results suggested that occupant satisfaction increased with the semi-automatic and manual modes of operation [66]. Eighty-five percent of the participants judged the overall lighting to be comfortable in the manual mode, while 78% felt similarly about the semi-automatic mode, and 57% about the automatic mode.…”
Section: Integrated Lighting and Shading Control Systemsmentioning
confidence: 94%
“…In a mock office, Vine et al [66] evaluated workers' response to a prototype integrated photocontrolled venetian blind/dimmable lighting system designed to optimise daylight admission in an office building. Fourteen workers aged between 40-49 were tested for 3 h over a 2-week period in July under mostly sunny conditions during which the blind/lighting system was activated to operate for 1 h in three modes of operation: Manual on/off operation of lighting and blinds during which users were allowed to adjust the blinds and lights according to their preference; Automatic operation of the integrated system with a design illuminance 540-700 lux, 11% base dimming load with turn-off capability after a 10-min delay with sufficient daylight, and non-retractable blinds designed to block direct sun; and semi-automatic operation with user-preference setting of blinds and lights via a remote control, which allowed users to set the indoor illuminance level between 240-1650 lux.…”
Section: Integrated Lighting and Shading Control Systemsmentioning
confidence: 99%
“…Comfort Working space [13] 500 Comfortable Office work [14] 500 Comfortable Office work [15] 840-2146 (morning) 840-2146 (morning) Comfortable Office work [4,5,15] 782-1278 (afternoon) 782-1278 (afternoon) Comfortable 700-1800 700-1800 Comfortable Computer work [16] 100-2000 100-2000 Useful Daylight Illuminance Any types of work [12] Switchable glazing includes electrochromic (EC) [17][18][19], gasochromic [20], thermochromic [21], thermotropic [22,23], liquid crystal (LC) [24], suspended particle device (SPD) [25][26][27][28] and phase change materials (PCM) [29]. These glazing can be electrically, thermally, or chemically actuated.…”
Section: Introductionmentioning
confidence: 99%
“…Vine et al studied the user's preferences for different blind systems (from automatic to manual). They found that users largely preferred the manual systems and complained about the too dim lit environment caused by the automatic blind system [17].…”
Section: Introductionmentioning
confidence: 99%